Chapter 15 Nitrates and Methemoglobinemia - Fossen Johnson, Sarah (Taylor & Francis, 2022)
Methemoglobinemia is characterized by a blue color to the skin, hypoxia that does not respond to administered oxygen, chocolate-colored blood, and shortness of breath. There are two main types of methemoglobinemia. The first type, congenital, is a genetic disease that can vary from very few minor symptoms to a severe disorder with significant neurological problems. The second type is acquired methemoglobinemia. This type of methemoglobinemia is characterized by exposure to an oxidizing agent, pharmaceutical, or chemical that can create transitory methemoglobinemia. Although it is transient, it can still be severe depending on what percentage of hemoglobin is converted to methemoglobin. At levels above 70 percent it can be fatal. Nitrate is one example of a chemical that can cause methemoglobinemia. After ingestion, the nitrate is converted to nitrite in the back of the mouth. Nitrite can then enter the bloodstream where it interacts with hemoglobin. The human body has two enzyme systems to keep the concentration of methemoglobin low, but those systems can be overwhelmed, allowing for methemoglobinemia to develop. There are several sources of nitrite and nitrate: some pharmaceuticals, contaminated water, prepackaged food, preserved meats, and vegetables such as zucchini and spinach.